Haplotype of receptor for advanced glycation end products is associated with arterial stiffness in essential hypertension. (25th November 2020) - Mahmud, A; Zhou, S; Yasmin, Y; Spiers, J.P; Feely, J; Silke, B
Abstract: Background: What causes us to age has been extensively explored. The receptor for AGEs (RAGE) expression is up-regulated in atherosclerotic plaques and its activation leads to oxidative stress, cytokine and adhesion molecule formation, activation of nuclear factor-κB and cell apoptosis. We hypothesized that genetic variation in the RAGE receptor may be associated with arterial stiffness. Methods: 309 untreated hypertensive subjects were tested for genotypes of –374T>A and –429T>C polymorphisms with polymerase chain reaction (PCR)-restriction fragment length polymorphism (RFLP). Arterial stiffness was measured as pulse wave velocity (PWV), augmentation index (AIx) and central aortic blood pressure (BP). Data was analysed using JMP Version 13 (SAS for Windows). Results: Both polymorphisms were in Hardy-Weinberg equilibrium. The –374A A allele carriers had significantly lower aortic systolic BP (143±2 vs. 154±1, p<0.001) while –429C allele carriers had lower aortic systolic BP (151±1 vs. 157±2, p<0.01) compared with T carriers. –429C allele carriers had lower PWV compared to 429TT individuals (8.86±1 vs. 10.70±2.5). –374A allele carriers had lower PWV compared to 374TT individuals (9.7±1.43 vs. 10.65±2.6). Subjects with the AC haplotype had the lowest and those with the TT haplotype the highest PWV and aortic BP than any of the other haplotypes containing one or more of the at-risk alleles. Conclusions: The combined effect of the two genotypes was additive with AA homozygotes of –374T>A and C allele carriers of –429T>C and the haplotype AC, associated with lowest aortic BP and arterial stiffness. Funding Acknowledgement: Type of funding source: None